Asymmetric snubberless current-fed full-bridge isolated DC-DC converters - Kosenko Roman; Blinov Andrei; Vinnikov Dmitri; Chub Andrii (Electrical, Control and Communication Engineering, 2018)
This paper presents two isolated current-fed fullbridge DC-DC converters that can be used to interface a lower voltage source into a DC bus of higher voltage. The first topology uses a resonant circuit to force current redistribution between low-voltage-side transistors and a passive rectifier. The second topology utilizes an active rectifier with secondary modulation to achieve the same goal. The resonant circuit can be formed by using transformer leakage inductance and the parasitic capacitances of the switches. The converters feature soft switching of semiconductors over a wide range of operating conditions. This is achieved with decreased energy circulation when compared to existing topologies with symmetric control and with fewer semiconductors than in those with phase-shift control. The topologies can be implemented in renewable, supercapacitor, battery, fuel cell, and DC microgrid applications. Steady-state operation and design aspects of the converters are presented and verified experimentally with 400 W prototypes